Attenuation of wave-induced groundwater pressure in shallow water. Part 2. Theory - Stanisław R. Massel; Anna Przyborska; Michał Przyborski (Oceanologia, 2005)
In this Part 2 of the paper (Part 1 was published by Massel et al. 2004) an exact close-form solution for the pore-water pressure component and velocity circulation pattern induced by surface waves is developed. This comprehensive theoretical model, based on Biot's theory, takes into account soil deformations, volume change and pore-water flow. The calculations indicate that for the stiffness ratio G/E'w ≥ 100, the vertical distribution of the pore pressure becomes very close to the Moshagen & Tørum (1975) approach, when the soil is rigid and the fluid is incompressible.     The theoretical results of the paper have been compared with the experimental data collected during the laboratory experiment in the Large Wave Channel in Hannover (see Massel et al. 2004) and showed very good agreement. The apparent bulk modulus of pore water was not determined in the experiment but was estimated from the best fit of the experimental pore-water pressure with the theoretical one. In the paper only a horizontal bottom is considered and the case of an undulating bottom will be dealt with in another paper.